2008
DOI: 10.1073/pnas.0804105105
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing fewer than 10 mouse T cells with an enhanced firefly luciferase in immunocompetent mouse models of cancer

Abstract: Antigen specific T cell migration to sites of infection or cancer is critical for an effective immune response. In mouse models of cancer, the number of lymphocytes reaching the tumor is typically only a few hundred, yet technology capable of imaging these cells using bioluminescence has yet to be achieved. A combination of codon optimization, removal of cryptic splice sites and retroviral modification was used to engineer an enhanced firefly luciferase (ffLuc) vector. Compared with ffLuc, T cells expressing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 38 publications
3
168
0
2
Order By: Relevance
“…Stable BTIC lines expressing enhanced firefly luciferase (effLuc) and eGFP were generated using a self-inactivating lentiviral vector system as described previously (28,29). BT73R and BT206R are temozolomide-resistant BTIC lines generated from parental BT73 and BT206.…”
Section: Btic Lines Tissue Culture and Reagentsmentioning
confidence: 99%
“…Stable BTIC lines expressing enhanced firefly luciferase (effLuc) and eGFP were generated using a self-inactivating lentiviral vector system as described previously (28,29). BT73R and BT206R are temozolomide-resistant BTIC lines generated from parental BT73 and BT206.…”
Section: Btic Lines Tissue Culture and Reagentsmentioning
confidence: 99%
“…To overcome this, a wide variety of signal amplification approaches has been proposed to enhance in vivo detection limits. Rabinovich and colleagues [23] developed an improved optical reporter vector system containing an engineered luciferase enzyme obtained through codon optimization techniques, such as insertion of Woodchuck hepatitis virus in the viral backbone to enhance exportation of mRNA to the cytoplasm and addition of a (G 3 S) 2 linker located at the 3′ portion of the internal ribosomal entry site sequence to avoid abnormal RNA folding. In this result, an increase of more than 100-fold in the luciferase activity was found in T cells infected with an enhanced firefly luciferase retrovirus (v-effLuc), compared with general firefly luciferase retroviral vector (v-ffLuc)-infected T cells.…”
Section: Improvement Of In Vivo Sensitivity Of Optical Imaging For Trmentioning
confidence: 99%
“…BLI could track migration to sites of inflammation and measure the life span of adoptively transferred T cells for tumor immunotherapy [79]. Rabinovich et al [80] developed an enhanced version of FLuc that can be transduced into primary mouse T cells and could provide sufficient sensitivity in tracking <10,000 T cells within living mice. Edinger et al [81] demonstrated homing of cytokine induced killer cells derived from splenocytes, which were retrovirally transduced with both green fluorescent protein and FLuc, to sites of tumor growth followed by tumor eradication.…”
Section: Tracking Of Immune Cellsmentioning
confidence: 99%